Capacity and Adequacy: Explicating Voting Behavior in A Multilevel and Concurrent Local Election - Wawan Sobari (Journal of Politics and Policy, 2019)
This qualitative case study explores voting behavior in a multilevel (municipality and province) and concurrent local election in the Municipality of Malang. Previous researches on concurrent local election in Indonesia revealed a number of relevant factors elucidating voters’ choices, namely vote-buying (Fossati et al., 2016), social identity (Kristianus, 2016), intensity of meeting with candidates (Ramadhany, 2017), and the blater character of incumbent (friendly and close to commoners) (Sobari, 2018).  The study extends previous findings through exposure to voting behavior that the capacity to vote and the adequacy of information about candidates are two converging factors explaining similarities and differences in the considerations for voting. The capacity demonstrates ability in making electoral decision, mainly referring to rational choice arguments. It is supported by the adequacy of information about the profile of candidates for mayors and governors along with their proposed vision, missions and programs. On the contrary, the lack of knowledge about candidates' profiles and their platforms contribute to the emergence of trivial voters who simply exercised their voting rights (alakadarnya) or without adequate consideration, especially in selecting candidates for governor. Furthermore, this research echoes Mondak and Huckfeldt’s study (2006) that information about candidate’s integrity is a rational argument for electoral decision, especially in the 2018 Local Election of Malang. Key words: local election, multilevel and concurrent, integrity, malang, indonesia.